P-405 Assessing women's preferences in a novel intrauterine device designed to monitor the womb environment in real time: A discrete choice experiment. (30th June 2022) - Ng, K.Y.B; Evans, R; Mentzakis, E; Cheong, Y
Abstract: Study question: What factors influence a woman's decision to use an intrauterine device designed to monitor the uterine environment? Summary answer: Willingness to use a novel intrauterine device to monitor the in-vivo uterine environment is mostly influenced by its ability to guide treatment of reproductive failures. What is known already: There is increasing evidence suggesting that the intrauterine environment is essential for successful implantation and placentation. The University of Southampton, in conjunction with an industry partner, are developing an intrauterine device which has the potential to monitor the temperature, pH and dissolved oxygen in real time in the uterus, with the aim of supporting those with reproductive failures. The device is similar in shape and size to a contraceptive coil, and has an accompanying wearable garment with an information receiver to collect data. This study aims to explore factors that are of importance to potential users of the intrauterine device. Study design, size, duration: A discrete choice experiment (DCE) was conducted; DCE is a preference elicitation method whereby individuals reveal their preference over selected attributes of a product in a series of pair-wise choices of hypothetical alternative products. Choice sets consisted of two hypothetical intrauterine devices described via four attributes: length of use, information obtained and its use in guiding treatment, risk of complications and discreteness of the information receiver. Ethical approvals were obtained (ERGO 49115, REC 19/IEC08/0036). Participants/materials, setting, methods: 361 women of reproductive age (18-50 years), who were wishing to achieve a pregnancy now or sometime in the future were recruited at Princess Anne Hospital in Southampton. A fractional factorial design was used to estimate effects of the four attributes, using 18 pair wise choice sets that identified all main effects and selected two-way interactions, blocked into two blocks of 9 choice sets each. Conditional and mixed logit models were used to analyse responses. Main results and the role of chance: Analysis was performed through conditional and mixed logit models with similar results. Overall, women prefer a device which stays in the uterus for a shortest length of time, provides information that guides treatment in all cases, has the lowest risk of complications, and has an information receiver which is completely discrete. Women placed the most importance on obtaining information to guide treatment in all cases (conditional logit co-efficient 2.771), followed by having a completely discrete device (1.104), reducing risk of complications by 1% (0.184) and lastly decreased length of time by 1 day (0.0150). All co-efficients p < 0.01. Latent class conditional logit assigns participants to two classes with 27.4% in Class 1 who are less likely to have higher education (co-efficient -0.660, 95% CI -0.967 and -0.353), and less likely to qualify for NHS funded IVF (co-efficient -0.709, 95% CI -1.065 and -0.353) compared to Class 2. Those in Class 2 placed 1.7 times more importance on a device whose information guided treatment in all cases and a 1% decrease in complications risk was nearly 15 times more attractive. Limitations, reasons for caution: Hypothetical bias may lower external validity. Although we obtained data on the 'stated' preferences within the hypothetical choice sets, we were not able to capture the 'actual' preferences of the women from this study. Wider implications of the findings: Women placed most importance on having a device that obtains information to guide treatment and are willing to use the device for a longer length of time, have a device with higher risk of complications and an indiscrete device if it can provide direction for treatment of their reproductive disorder. Trial registration number: N/A